2016
DOI: 10.1002/anie.201607309
|View full text |Cite|
|
Sign up to set email alerts
|

Topological Polymer Chemistry Enters Surface Science: Linear versus Cyclic Polymer Brushes

Abstract: The cyclic polymer topology strongly alters the interfacial, physico-chemical properties of polymer brushes, when compared to the linear counterparts. In this study, we especially concentrated on poly-2-ethyl-2-oxazoline (PEOXA) cyclic and linear grafts assembled on titanium oxide surfaces by the "grafting-to" technique. The smaller hydrodynamic radius of ring PEOXAs favors the formation of denser brushes with respect to linear analogs. Denser and more compact cyclic brushes generate a steric barrier that surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
169
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 48 publications
6
169
2
2
Order By: Relevance
“…[1][2][3][4][5][6][7] Extensive work has been conducted to overcome the synthetic constraints due to the unfavorable entropy of cyclization. Herein we report the use of the Piers-Rubinsztajn reaction for the one-step synthesis of cyclic polysiloxanes with novel structural features.S pecifically,t he B(C 6 F 5 ) 3 -catalyzed coupling of various organic tris(dimethylsiloxy)silane and trialkoxysilane compounds generated as eries of cyclic polysiloxanes with cyclotetrasiloxane subunits.The thiolated cyclic polymers were also shown to be effective in directing the circular assembly gold nanoparticles.T he presence of constrained rings in the backbone is unprecedented and may offer opportunities for novel applications of these cyclic polymers.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Extensive work has been conducted to overcome the synthetic constraints due to the unfavorable entropy of cyclization. Herein we report the use of the Piers-Rubinsztajn reaction for the one-step synthesis of cyclic polysiloxanes with novel structural features.S pecifically,t he B(C 6 F 5 ) 3 -catalyzed coupling of various organic tris(dimethylsiloxy)silane and trialkoxysilane compounds generated as eries of cyclic polysiloxanes with cyclotetrasiloxane subunits.The thiolated cyclic polymers were also shown to be effective in directing the circular assembly gold nanoparticles.T he presence of constrained rings in the backbone is unprecedented and may offer opportunities for novel applications of these cyclic polymers.…”
mentioning
confidence: 99%
“…[4,6] This changed greatly with the introduction of click chemistry in the synthesis of cyclic polymers as pioneered by Grayson. These results highlight the impact of the cyclic polymer topology on the interaction of PEI with DNAa sw ell as with biological systems,namely cells.In two very recent papers of Benetti et al, [9,10] cyclic polymer coated surfaces and nanoparticles were demonstrated to be superior over their linear counterparts with regard to antifouling behavior and stabilization, respectively.C-PEtOx [*] B. Verbraeken,P rof. Continuous feeding of al inear polymer precursor with azido and alkyne chain end-functionalities into as olution of copper(I) catalyst for the copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) allows the efficient synthesis of cyclic polymers in larger quantities,t hereby providing sufficient material to investigate their application potential.…”
mentioning
confidence: 99%
“…Assemblies of cyclic polymers have recently emerged as advantageous compared to the commonly applied linear brushes.T his is especially valid when cyclic polymers are confined on ap lanar inorganic surface, [10] yielding cyclic polymer brushes,o ra tt he exposed interface of blockcopolymer micelles. Assemblies of cyclic polymers have recently emerged as advantageous compared to the commonly applied linear brushes.T his is especially valid when cyclic polymers are confined on ap lanar inorganic surface, [10] yielding cyclic polymer brushes,o ra tt he exposed interface of blockcopolymer micelles.…”
mentioning
confidence: 99%
“…The ligand surface coverage (grafting density, s), the colloidal stability in pure water and in physiological buffer solution, the temperature-dependent behavior, and the interaction of the prepared NPs with solution proteins were analyzed, comparing, for the first time,core-linear and core-cyclic polymer shell NPs.T he choice of PEOXAsa ss hell-forming ligands is especially relevant, since the interest in this polymer has been rising considerably as apossible replacement for PEGs in bio/ nanomaterials preparations,i ncluding the fabrication of antifouling coatings on flat surfaces [20,21] and the synthesis of stabilizers for metallic NPs. [25] Highly monodisperse and monocrystalline,o leic acidstabilized Fe 3 O 4 NPs (OA-NPs) with adiameter of 9nmwere synthesized through thermal decomposition of Fe(CO) 5 , following am odified protocol by Hyeon et al [26] Narrowly dispersed, ND-functionalized cyclic PEOXAs, as well as their linear counterparts were synthesized as previously reported [10] by cationic ring opening polymerization (CROP), using opportunely chosen initiator and terminator species,followed by post-modification ( Figure 1a,i -iv,a nd the Supporting Information for experimental details). [24] Notably,a ne fficient passivation of Fe 3 O 4 cores by robustly anchored and dense polymer shells prevents the generation of cytotoxic reactive oxygen species (ROS), which typically cause protein and DNAo xidation.…”
mentioning
confidence: 99%